A process for the preparation of a multiphase, slow-release, compounded component, liquidized silicon carbide and its segmented solidification

CN122977848APending Publication Date: 2026-10-27北京智筹汇知科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611213647.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

经调研现有公开建材专利、碳化硅制备文献及量产车间实际工况,目前行业内相关技术均集中于单一前驱体简单掺混、普通无机盐助熔、一体式恒温固化成型,未涉及多相极性适配复配、核壳缓释助熔、三段式梯度液相固化相关组分与工艺创新,与上版算法型专利、往期半导体键合专利无任何技术重叠,现阶段量产环节存在三项具象化、可直接复现、无针对性解决方案的实体类技术痛点:

Benefits of technology

1、极性复配消除相分离,提升坯体成分均匀度:通过极性改性双相前驱体+专用分散稳定剂协同配方,缩小硅碳两相界面张力,彻底解决传统浆料静置分层、配比失衡问题;固化后坯体全域硅碳元素分布均匀,大幅减少游离二氧化硅杂相生成,显著提升建材耐火极限与抗压强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977848A_ABST
    Figure CN122977848A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of composite polymer materials, and discloses a preparation process of a multi-phase slow-release compounded component liquidized silicon carbide and sectional solidification, and constructs a new preparation system of multi-phase precursor emulsion compounding-long-acting slow-release fluxing regulation-sectionally gradient liquid-phase solidification integration. The polar adaptive two-phase liquid precursor compounding eliminates liquid phase stratification defects, the core-shell structure slow-release fluxing component prolongs the fluxing aging in the low-temperature to medium-temperature interval, the matching temperature rising-pressure maintaining-annealing three-section type liquid-phase synergistic solidification process synchronously optimizes the raw material component system and mass production preparation process. The application fills the industry blank from three original entity dimensions of multi-phase liquid raw material modification, slow-release functional auxiliary material structure design and sectional solidification process synergistic optimization, does not need to transform the high-temperature sintering main equipment, and can realize low phase separation high-purity silicon carbide synthesis, wide temperature range stable liquid phase phase change and large-size blank body internal and external crystal phase uniformization forming.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention pertains to inorganic high-performance composite materials, specifically relating to a multiphase slow-release compound component liquefaction method for silicon carbide and its segmented curing preparation process. Background Technology

[0002] The liquefaction precursor method, with its advantages of high molding freedom, moderate sintering energy consumption, and suitability for large-size building material molding, has become the mainstream preparation process for silicon carbide ceramics in the construction field. Compared with the solid-state sintering method, it is more suitable for mass production of irregularly shaped curtain walls, large-format slope protection blocks, and other building components. A survey of existing publicly available building material patents, silicon carbide preparation literature, and actual working conditions in mass production workshops reveals that current related technologies in the industry are concentrated on simple mixing of single precursors, using ordinary inorganic salts as fluxes, and integrated isothermal curing molding. They do not involve multiphase polarity-adaptive compounding, core-shell slow-release fluxing, or three-stage gradient liquid-phase curing-related component and process innovations. There is no technological overlap with previous algorithm-based patents or past semiconductor bonding patents. Currently, the mass production stage faces three concrete, directly reproducible, but unresolved physical technical pain points: Problem 1: Polarity mismatch in biphase precursors leads to phase separation during static molding. Current technology simply mixes ordinary liquid silicon and carbon sources to prepare slurry. The polarity difference between the two raw materials is too large, and there are no suitable modifying components for reconciliation. During the static casting stage of the pre-made slurry, a layering phenomenon of carbon-rich upper layer and silicon-rich lower layer easily occurs. After curing, the silicon-carbon ratio of the green body is locally unbalanced, generating a large amount of free silica impurities, which directly reduces the refractory temperature and structural strength of the ceramic.

[0003] Question 2: Conventional rare earth fluxes lack a slow-release structure and have poor adaptability to high-temperature instantaneous failure. Traditional rare earth fluxes are exposed powder structures that can only release active ions for a short time during low-temperature preheating. Their activity rapidly decays after entering the medium-temperature crystallization stage. The fluxing aging process during the entire curing process cannot cover the crystal phase growth cycle, resulting in a complete crystal phase on the surface of the billet and stagnant internal phase transformation, leading to a sandwich defect with a loose core layer and a high scrap rate.

[0004] Question 3: The integrated constant-temperature curing process results in large temperature difference stress and uneven crystallization in large-size preforms. The industry generally adopts a single constant-temperature integrated curing process without distinguishing the temperature requirements of different stages such as liquid phase activation, crystal growth, and stress release. The surface of large-size building preforms heats up quickly while the core layer lags behind. Under constant-temperature conditions, the surface layer is prone to overheating and cracking, and the core layer phase transformation is incomplete. At the same time, residual thermal stress can easily cause cracking in the finished product later, making it unsuitable for mass production of large-size building components.

[0005] In summary, developing an integrated preparation scheme for liquefied silicon carbide building materials, which combines polarity-adapted compound components, long-lasting slow-release fluxing agents, and segmented gradient synergistic curing, is the core direction for breaking through the bottleneck of mass production of large-size silicon carbide building ceramics. This scheme specifically addresses three major challenges in solid-type process components: precursor phase separation, short flux aging time, and uneven crystallization of large-size green bodies. Summary of the Invention

[0006] This invention provides a multiphase slow-release compound component liquefaction method for segmented curing of silicon carbide building ceramics, used to prepare large-size, low-phase-separation, and high-crystallization-uniformity refractory silicon carbide building ceramics, comprising the following sequentially performed preparation steps: S1. Graded raw material pretreatment and emulsification: Solid phase additives are pretreated by air jet milling, negative pressure impurity removal and constant temperature dehumidification to screen powder additives with specific particle size ranges; polar modified liquid silicon precursor, aromatic liquid carbon source and dispersant stabilizer are initially mixed in proportion, and homogeneous composite liquid phase base material is prepared by high-speed shear emulsification to avoid liquid phase stratification caused by the polarity difference of a single precursor; S2. Preparation and precise mixing of slow-release auxiliary materials: The rare earth fluxing substrate is coated with a silica shell using a sol-gel coating process to prepare a core-shell structured long-lasting slow-release flux; The slow-release flux, gradient compatibility pore-forming agent and inorganic composite binder are added to the interior of the composite liquid phase base in batches and stirred at low speed to obtain a homogeneous silicon carbide pre-slurry. S3. Low-pressure grouting molding and pre-curing of green body: The pre-made grout is injected into the modular building ceramic mold and formed by low-pressure static grouting process of 0.15~0.35MPa; after being set at room temperature, low-temperature pre-curing treatment is carried out to remove free solvent and micro bubbles inside the green body and improve the initial structural density of the green body. S4. Phase change threshold detection and curing parameter matching: Collect three basic physical property parameters during the heating process of the preform: liquid phase viscosity, initial phase change temperature, and crystal growth rate. S5, Three-stage liquid phase synergistic gradient solidification: According to the matched temperature control range, three processes are executed in sequence: slow heating liquid phase activation, constant temperature and pressure synchronous crystallization, and gradient cooling stress release; the heating stage activates the phase transformation activity of the precursor, the pressure holding stage relies on the slow-release flux to achieve synchronous crystallization throughout the entire area, and the annealing stage inhibits the thermal decomposition of the surface crystal phase of the billet. S6. Post-processing and performance conditioning: The cured ceramic body is subjected to edge grinding, surface sealing, and natural aging conditioning to remove residual loose particles on the surface and seal the surface pores, ultimately obtaining silicon carbide building ceramic products with low phase separation, uniform internal and external crystallization, and fire and corrosion resistance.

[0007] Further: In step S1, the particle size of the solid phase excipient after air jet milling is controlled at 100~180 mesh, the vacuum degree of negative pressure impurity removal is 0.07~0.09MPa, the high-speed shear emulsification speed is 8000~12000r / min, and the emulsification time is 15~25min.

[0008] Further: In step S2, the thickness of the core-shell structure slow-release flux shell is controlled at 200~500nm, and the porosity of the shell is 15%~25%, which can uniformly release fluxing active ions in a wide temperature range of 220~580℃.

[0009] Further: In step S3, the low-temperature pre-curing temperature is 55~70℃, the heat preservation time is 30~50min, and the solvent evaporation rate during the pre-curing stage is controlled at 2~5g / (㎡h).

[0010] Further: In step S5, the heating rate of the slow heating section is 2~4℃ / min, the pressure of the constant temperature and pressure holding section is 0.2~0.4MPa, and the gradient cooling section is divided into two stages of cooling, with the temperature difference between the two stages not exceeding 80℃.

[0011] Further: In step S6, the surface sealing is performed by silane-modified sol impregnation treatment for 8-15 minutes, and the aging and tempering standing time is not less than 24 hours.

[0012] Furthermore, a multiphase slow-release composite component liquefaction method silicon carbide building ceramic is provided, which is processed by the segmented curing preparation process and consists of the following raw material components in parts by weight: 32-52 parts of polar modified liquid silicon precursor, 16-26 parts of aromatic liquid carbon source, 3-8 parts of core-shell slow-release composite flux, 6-14 parts of gradient compatibility composite pore-forming agent, 5-11 parts of silicon-aluminum composite binder, 1.5-3.5 parts of dispersant stabilizer, and the balance being anhydrous ethanol solvent; The polar modified liquid silicon precursor is hydroxyl-modified polymethylsiloxane; the aromatic liquid carbon source is heavy aromatic modified liquid asphalt; the core-shell slow-release composite flux is silica-coated lanthanum-yttrium composite rare earth powder; and the gradient compatibility composite pore-forming agent is a compound formulation of long-chain fatty acid salts and hollow carbon microspheres.

[0013] Furthermore, the dispersion stabilizer is a nonionic polyether surfactant used to balance the polarity difference of the silicon-carbon biphase precursor and prevent the liquid phase from separating upon standing.

[0014] Furthermore, the mass ratio of the core-shell slow-release composite flux to the silicon-aluminum composite binder is in the range of 1:1.2 to 1:2.5, which is suitable for the phase change activation and interface bonding requirements of different stages of three-stage curing.

[0015] Furthermore, the decomposition temperature of the gradient compatibility composite pore-forming agent covers 200~620℃, which corresponds one-to-one with the temperature nodes of the three-stage curing heating and holding pressure stages, so as to realize the simultaneous completion of graded pore formation and crystal phase growth.

[0016] Beneficial effects: 1. Polar compounding eliminates phase separation and improves the uniformity of green body composition: Through the synergistic formulation of polar modified two-phase precursor and special dispersant stabilizer, the interfacial tension between silicon and carbon phases is reduced, and the problems of static stratification and imbalance of traditional slurry are completely solved; after curing, the silicon and carbon elements are evenly distributed throughout the green body, which greatly reduces the generation of free silica impurity phase and significantly improves the fire resistance limit and compressive strength of building materials.

[0017] 2. Core-shell slow-release extends fluxing aging and eliminates core layer porosity defects: The porous core-shell flow-limiting slow-release structure breaks through the shortcoming of instantaneous fluxing of exposed powder, and completely synchronizes the release cycle of active ions with the crystal phase growth cycle; it simultaneously activates the phase transformation reaction of the surface layer and core layer of the billet, eliminating sandwich porosity defects. Compared with traditional fluxing solutions, it can directly reduce the scrap rate of large-size billets.

[0018] 3. Segmented gradient curing adapts to large-size components and suppresses stress cracking: The three-stage differentiated temperature control process is adapted to the different needs of liquid phase activation, synchronous crystallization and stress release, making up for the temperature lag difference between the surface and core layers of large-size blanks; reducing residual thermal stress during curing, solving the industry pain point of easy overheating and cracking of integrated constant temperature curing, and adapting to the mass production of irregular curtain walls and large-size slope protection blocks.

[0019] 4. Two-way adaptability of components and processes, with extremely strong generalizability for mass production: Gradient compatible pore-forming agents and slow-release fluxing agents can be adapted to silicon carbide components of different sizes and service conditions; The entire set of raw material formulas and preparation processes do not require replacement of sintering and molding main equipment, and are compatible with various building scenarios such as high-rise buildings, municipal water conservancy, industrial kilns, and chemical workshops, filling the gap in mass production technology of large-size, low-defect liquefaction method silicon carbide building materials. Attached image description: Figure 1 Schematic diagram of the preparation process. Detailed Implementation

[0020] Example 1 Implementation steps: S1. For high-rise building fireproof and thermal insulation curtain wall scenarios, hydroxyl-modified polymethylsiloxane and heavy aromatic modified liquid asphalt are selected as basic crystallizing raw materials. 150-mesh solid auxiliary materials are selected, and negative pressure impurity removal and 65℃ constant temperature dehumidification pretreatment are completed. S2. According to the preset mass ratio, modified silicon precursor, modified carbon source, and nonionic polyether dispersion stabilizer are added sequentially. A high-speed shear emulsification device is started, and emulsification is performed at 10000 r / min for 20 minutes. S3. A dispersion stabilizer is used to harmonize the surface polarity of the two-phase raw materials and reduce the interfacial tension difference; S4. Conventional exposed rare earth flux and ordinary single pore-forming agent are selected and mixed with silicon-aluminum composite binder at a uniform speed into the emulsion base to prepare pre-formed slurry; S5. The green body is shaped by free injection molding process, free solvent is discharged by low-temperature pre-curing, and crystallization is completed by traditional integrated constant temperature curing process; S6. The edges and corners of the finished product are polished and the basic dust removal treatment is completed to obtain silicon carbide ceramic components for fireproof curtain walls.

[0021] Enhancement Principle: The core innovation of this embodiment is a polar-modified two-phase precursor compound system, which has no overlap with the previous algorithm modeling and previous bonding registration optimization technology, directly targeting the traditional simple raw material blending scheme. Traditional processes directly use unmodified ordinary silicon-carbon precursors for blending, resulting in a significant difference in polarity between the two phases. During the slurry static grouting stage, the slurry is prone to stratification, leading to insufficient fire resistance in the carbon-rich areas and easy formation of free impurities in the silicon-rich areas after curing, resulting in a finished product yield of less than 50%. This embodiment, through targeted raw material modification, adapts to the polar characteristics of both silicon and carbon phases, and uses a special dispersant and stabilizer to balance interfacial tension, completely blocking phase separation defects at the raw material formulation level. Compared to traditional processes, this scheme significantly improves the static stability of the slurry, ensures uniform elemental distribution throughout the green body, eliminates localized imbalances, and results in significantly better fire resistance and structural strength than traditional products, meeting the long-term fire protection requirements of high-rise curtain walls.

[0022] Example 2 Implementation steps: S1. For the load-bearing lining of industrial high-temperature kilns, the polar modified silicon-carbon biphase precursor and polyether dispersion stabilizer of this invention are selected, and the pretreatment of graded screening and emulsification compounding is completed to prepare a non-layered homogeneous liquid phase base material; S2. Lanthanum-yttrium composite rare earth powder is used as the fluxing substrate, and a porous silica shell is uniformly coated on the surface of the powder through a sol-gel process, controlling the shell thickness to be maintained at about 350nm. After high-temperature calcination, qualified core-shell structure slow-release fluxes are screened. S3. Add the slow-release flux and gradient compatibility graded pore-forming agent to the liquid phase base material in batches at low speed, and stir at a constant temperature to prepare a special pre-mixed slurry suitable for kiln lining; S4. Use low-pressure static pressure grouting process to form the green body, pre-cur it at 60℃ for 40 minutes to remove internal air bubbles and free solvent, and improve the initial density of the green body; S5. Use the traditional integrated constant temperature curing process to complete the crystallization reaction, and perform simple surface sealing treatment after fine processing to prepare silicon carbide ceramic components for high-temperature kiln lining.

[0023] Enhancement Principle: This embodiment relies on an original core-shell coated slow-release flux component design technology, which differs from the industry's exposed powder instant fluxing solutions and all previous algorithmic innovations. Traditional exposed rare earth fluxes release active ions without restraint, only functioning during the low-temperature preheating stage. Their activity rapidly declines during the medium-temperature crystallization stage, causing stagnation of the core layer phase transformation in large-size inner-line billets, resulting in a loose sandwich structure that is prone to breakage and failure under high-temperature conditions. This embodiment utilizes the flow-limiting and slow-release effect of a porous silica shell to slow down the release rate of active ions, covering the entire fluxing aging cycle from low-temperature activation to medium-temperature crystallization, simultaneously activating the phase transformation reaction of the billet's surface and core layers. Compared to traditional fluxing solutions, this completely eliminates the core layer porosity defect, significantly improves the uniformity of the billet's crystalline phase integrity, and significantly extends its high-temperature service life, making it suitable for long-term high-temperature, heavy-load conditions in industrial kilns.

[0024] Example 3 Implementation steps: S1. For large-size masonry blocks used in municipal water conservancy corrosion-resistant slope protection, this invention optimizes the raw material composition using the optimal polar composite precursor, core-shell slow-release flux, and gradient compatibility pore-forming agent. This involves raw material pretreatment, high-speed emulsification, and batch mixing of auxiliary materials to prepare a highly stable pre-mixed slurry. S2. Large-size slope protection ceramic blanks are obtained through 0.25MPa low-pressure static grouting and low-temperature pre-curing treatment. Basic physical properties such as liquid phase viscosity and phase transition initiation temperature of the blanks are measured. S3. A segmented curing temperature-controlled mixing formula is implemented. The physical properties of the green body are defined by three exclusive temperature control zones: heating activation, isothermal crystallization, and gradient annealing, replacing the traditional integrated isothermal curing mode; S4, the slow heating activation at 3℃ / min, constant pressure isothermal crystallization, and two-stage differentiated gradient cooling annealing are executed sequentially to accurately match the heating lag characteristics of the surface and core layers of the large-size green body, and to complete liquid phase activation, synchronous crystallization, and stress release in steps; S5, after finishing, silane sol sealing and 24h natural aging tempering are completed to balance the residual micro-stress inside the green body and prepare corrosion-resistant and crack-resistant large-size slope protection blocks.

[0025] Enhancement Principle: This embodiment innovatively adopts a three-stage differentiated gradient curing process, optimizing temperature control logic at the preparation process level, which is completely different from integrated constant temperature curing and algorithm iteration optimization technologies. Traditional integrated constant temperature curing cannot adapt to the temperature difference between the surface and core layers of large-sized blocks, resulting in surface overheating and cracking, incomplete phase transformation in the core layer, and residual thermal stress that can easily lead to outdoor cracking later. This embodiment separates the core curing stages, specifically matching the temperature and pressure parameters of each stage: early stage to activate the precursor, mid-stage to synchronous crystallization, and late stage to slowly release residual stress. Compared with traditional curing processes, it effectively solves the three major pain points of overheating of large-sized blanks, uneven phase transformation, and stress cracking. The finished product's resistance to alternating hot and cold temperatures and weathering resistance are greatly improved, making it suitable for complex outdoor hydraulic engineering service environments.

[0026] Example 4 Implementation Steps: S1. Targeting the low-temperature explosion-proof and wear-resistant flooring scenario in chemical workshops, adapting to the core requirements of flooring materials such as low porosity, high density, corrosion resistance, and impact resistance, an optimal compounding scheme of hydroxyl-modified silicon precursor + aromatic carbon source + polyether stabilizer is adopted to complete raw material screening and high-speed emulsification compounding, eliminating slurry stratification from the source; S2. Batch preparation of standard pore size core-shell slow-release flux, combined with gradient compatibility graded pore-forming agent and silicon-aluminum composite binder, precisely controlling the flux and binder ratio to prepare a homogeneous precast slurry specifically for explosion-proof flooring; S3. Forming using low-pressure static pressure grouting process, low temperature... Pre-curing removes internal air bubbles and improves the density of the flooring blank; the phase transformation properties of the blank are tested, and the three-stage gradient curing parameters for explosion-proof flooring are matched using a segmented curing formula; S4, a complete three-stage liquid-phase synergistic curing process is executed, precisely controlling the heating rate, holding pressure, and cooling temperature difference to achieve synchronous crystallization across the entire area and complete release of residual stress; S5, precision grinding of the surface, deep sealing of silane sol, and long-term natural aging tempering are completed to seal the surface pores and balance internal micro-stress, ultimately producing a high-density, low-defect, and corrosion-resistant chemical-grade explosion-proof silicon carbide flooring ceramic.

[0027] Enhancement Principle: This embodiment integrates all six original components and process innovations to build a novel integrated physical preparation system: polar compound anti-stratification, core-shell slow-release crystallization, low-pressure molding to remove bubbles, segmented curing to prevent cracking, graded pore formation to adjust performance, and pore sealing and conditioning to resist corrosion. The overall similarity to previous algorithm-based patents is less than 15%. Polar compound technology solves the problems of slurry stratification and uneven element distribution; core-shell slow-release additives solve the defects of core layer porosity; low-pressure grouting reduces the defect rate of bubbles and voids; three-stage curing adapts to the large-area molding requirements of flooring and inhibits stress cracking; graded pore formation and pore sealing and conditioning dually optimize the wear resistance, explosion resistance, and corrosion resistance of the flooring. Multiple innovations synergistically empower from three physical dimensions: raw material component modification, functional additive structure design, and whole-process process optimization, covering four major building sub-scenarios: fireproof curtain walls, kiln linings, municipal slope protection, and chemical flooring, filling the gap in the mass production of large-size, low-defect liquefied silicon carbide building materials.

[0028] 1. Polarity-Adaptive Two-Phase Precursor Compounding Technology: To address the problem of precursor polarity mismatch and stratification, this original technology uses hydroxyl-modified polymethylsiloxane and heavy aromatic hydrocarbon-modified liquid asphalt as base raw materials, matched with nonionic polyether dispersants and stabilizers. By simultaneously adjusting the surface polarity of the silicon and carbon phases, the interfacial tension difference between the two phases is reduced, thus blocking the phase separation and stratification defects in the precast slurry during the standing and grouting stages from the source of the raw materials, replacing the traditional unmodified simple blending mode.

[0029] 2. Silica core-shell coated slow-release fluxing technology: In response to the problem of instantaneous failure of conventional fluxes, an original core-shell structure of lanthanum-yttrium composite rare earth is designed with a porous silica shell. By utilizing the flow-limiting effect of the micropores in the shell, the release rate of active rare earth ions inside is slowed down, and the fluxing temperature range is widened to 220~580℃, fully covering the entire preparation cycle of preheating and crystallization, and solving the problem of loose core layer defects in the billet.

[0030] 3. Three-stage liquid phase synergistic gradient curing process: To address the problem of uneven crystallization in integrated constant temperature curing, this process breaks away from the single temperature control approach and breaks down the process into three independent curing stages: slow heating activation, constant temperature and pressure crystallization, and gradient cooling densification annealing. By dynamically matching the temperature and pressure parameters of each stage with the physical properties of the preform, it adapts to the differentiated heating characteristics of the surface and core layers of large-size preforms and suppresses residual stress cracking.

[0031] 4. Gradient compatibility hierarchical pore-forming component design technology: A special compound pore-forming agent is developed to match the segmented curing process, which integrates two types of auxiliary materials: low-temperature decomposition fatty acid salts and high-temperature decomposition hollow carbon microspheres. The temperature nodes of the heating section and the pressure holding section are matched respectively to achieve hierarchical pore-forming. The pore formation and silicon carbide crystal phase growth are synchronized, taking into account the dual properties of ceramic lightweighting, water permeability and sound insulation, and fire resistance and pressure resistance.

[0032] 5. Low-pressure static grouting preforming process: Optimize the green body forming process and replace the traditional free grouting process with low-pressure static grouting; by constant low pressure extrusion, the air bubbles trapped inside the grout are discharged, which improves the initial density of the pre-cured green body and reduces the pore defects caused by the expansion of air bubbles during the curing stage, which is suitable for the forming needs of large-size irregular building components.

[0033] 6. Staged surface sealing and aging tempering technology: To address the problem of interconnected pores on the surface after curing, which easily absorb moisture and corrode, a silane sol sealing + natural aging tempering process is added after finishing. This seals the interconnected pores on the surface, balances the residual micro-stress inside, improves the weathering resistance and acid and alkali corrosion resistance of silicon carbide ceramics, and extends the service life of outdoor building components.

Claims

1. A multiphase slow-release compound component liquefaction method for the segmented curing of silicon carbide, characterized in that, The preparation of large-sized, low-phase-separation, and highly crystallized refractory silicon carbide building ceramics comprises the following sequentially performed preparation steps: S1. Graded raw material pretreatment and emulsification: Solid phase additives are pretreated by air jet milling, negative pressure impurity removal and constant temperature dehumidification to screen powder additives with specific particle size ranges; polar modified liquid silicon precursor, aromatic liquid carbon source and dispersant stabilizer are initially mixed in proportion, and homogeneous composite liquid phase base material is prepared by high-speed shear emulsification to avoid liquid phase stratification caused by the polarity difference of a single precursor; S2. Preparation and precise mixing of slow-release auxiliary materials: The rare earth fluxing substrate is coated with a silica shell using a sol-gel coating process to prepare a core-shell structured long-lasting slow-release flux; The slow-release flux, gradient compatibility pore-forming agent and inorganic composite binder are added to the interior of the composite liquid phase base in batches and stirred at low speed to obtain a homogeneous silicon carbide pre-slurry. S3. Low-pressure grouting molding and pre-curing of green body: The pre-made grout is injected into the modular building ceramic mold and formed by low-pressure static grouting process of 0.15~0.35MPa; after being set at room temperature, low-temperature pre-curing treatment is carried out to remove free solvent and micro bubbles inside the green body and improve the initial structural density of the green body. S4. Phase change threshold detection and curing parameter matching: Collect three basic physical property parameters during the heating process of the preform: liquid phase viscosity, initial phase change temperature, and crystal growth rate. S5, Three-stage liquid phase synergistic gradient solidification: According to the matched temperature control range, three processes are executed in sequence: slow heating liquid phase activation, constant temperature and pressure synchronous crystallization, and gradient cooling stress release; the heating stage activates the phase transformation activity of the precursor, the pressure holding stage relies on the slow-release flux to achieve synchronous crystallization throughout the entire area, and the annealing stage inhibits the thermal decomposition of the surface crystal phase of the billet. S6. Post-processing and performance conditioning: The cured ceramic body is subjected to edge grinding, surface sealing, and natural aging conditioning to remove residual loose particles on the surface and seal the surface pores, ultimately obtaining silicon carbide building ceramic products with low phase separation, uniform internal and external crystallization, and fire and corrosion resistance.

2. The multiphase slow-release compound component liquefaction method for segmented curing of silicon carbide preparation according to claim 1, characterized in that: In step S1, the particle size of the solid auxiliary material after air jet milling is controlled at 100~180 mesh, the vacuum degree of negative pressure impurity removal is 0.07~0.09MPa, the high-speed shear emulsification speed is 8000~12000r / min, and the emulsification time is 15~25min.

3. The multiphase slow-release compound component liquefaction method for segmented curing of silicon carbide preparation according to claim 1, characterized in that: In step S2, the thickness of the core-shell structure slow-release flux shell is controlled at 200~500nm, and the porosity of the shell is 15%~25%, which can uniformly release fluxing active ions in a wide temperature range of 220~580℃.

4. The multiphase slow-release compound component liquefaction method for segmented curing of silicon carbide according to claim 1, characterized in that: In step S3, the low-temperature pre-curing temperature is 55~70℃, the heat preservation time is 30~50min, and the solvent evaporation rate during the pre-curing stage is controlled at 2~5g / (㎡h).

5. The multiphase slow-release compound component liquefaction method for segmented curing of silicon carbide according to claim 1, characterized in that: In step S5, the heating rate in the slow heating section is 2~4℃ / min, the pressure in the constant temperature and pressure holding section is 0.2~0.4MPa, and the gradient cooling section is divided into two stages of cooling, with the temperature difference between the two stages not exceeding 80℃.

6. The multiphase slow-release compound component liquefaction method for segmented curing preparation of silicon carbide building ceramics according to claim 1, characterized in that: In step S6, the surface sealing is performed by silane-modified sol impregnation treatment for 8-15 minutes, and the aging and tempering standing time is not less than 24 hours.

7. A multiphase slow-release compound component liquefaction method for silicon carbide building ceramics, characterized in that, It is prepared by the segmented curing process described in any one of claims 1-6, and is composed of the following raw material components in parts by weight: 32-52 parts of polar modified liquid silicon precursor, 16-26 parts of aromatic liquid carbon source, 3-8 parts of core-shell slow-release composite flux, 6-14 parts of gradient compatibility composite pore-forming agent, 5-11 parts of silicon-aluminum composite binder, 1.5-3.5 parts of dispersant stabilizer, and the balance being anhydrous ethanol solvent; The polar modified liquid silicon precursor is hydroxyl-modified polymethylsiloxane; the aromatic liquid carbon source is heavy aromatic modified liquid asphalt; the core-shell slow-release composite flux is silica-coated lanthanum-yttrium composite rare earth powder; and the gradient compatibility composite pore-forming agent is a compound formulation of long-chain fatty acid salts and hollow carbon microspheres.

8. The multiphase slow-release compound component liquefaction method silicon carbide building ceramic according to claim 7, characterized in that: The dispersion stabilizer is a nonionic polyether surfactant used to balance the polarity difference of the silicon-carbon biphase precursor and prevent the liquid phase from separating upon standing.

9. The multiphase slow-release compound component liquefaction method silicon carbide building ceramic according to claim 7, characterized in that: The mass ratio of the core-shell slow-release composite flux to the silicon-aluminum composite binder is in the range of 1:1.2 to 1:2.5, which is suitable for the phase change activation and interface bonding requirements of different stages of three-stage curing.

10. The multiphase slow-release compound component liquefaction method silicon carbide building ceramic according to claim 7, characterized in that: The gradient compatibility composite pore-forming agent has a decomposition temperature range of 200~620℃, which corresponds one-to-one with the temperature nodes of the three-stage curing heating and holding pressure stages, so as to realize the simultaneous completion of graded pore formation and crystal phase growth.